Meningkatkan Motivasi Dan Hasil Belajar Siswa Melalui Contextual Teaching And Learning Pada Tema Lingkungan Di Kelas II SDN 2 Talise - Santje Amuntu; Amram Rede; Marungkil Pasaribu (Universitas Tadulako, 2016)
The study was classroom action research aimed to improve motivation and students learning outcomes in environment theme by implementing CTL. The research carried out at SDN 2 Talise with 22 students in academic year 2013-2014. The research consist of two cycles. Each cycles is supported by planning, action, observation, and reflection. The results showed that the student absorbing and classical learning completeness realized increasing from cycle I to cycle II. Teacher and student activities increasing where the teacher ativity in cycle I was in sound categoy in cycle II in good category,where as student’s activity in cycle I was in sufficient category but in cycle II was in good category. All the result can be concluded that the application of contextual learning can improve the outcome learning.